Web-Based Accounting Information System for Laundry Service Management - Arifin, Nofri Yudi (YCMM, 2025)
In the digital era, the utilization of information technology has become essential for various business sectors, including the laundry service industry. However, many laundry businesses still rely on manual record-keeping for managing transactions and finances, which can lead to recording errors, data loss, and difficulties in generating systematic financial reports. This study aims to design and develop a web-based accounting information system to help laundry businesses manage transactions and financial reports more effectively and efficiently. The development method used is the waterfall model, which includes the stages of requirements analysis, system design, program implementation, testing, and maintenance.The results indicate that the developed system enables administrators to manage transaction data, services, and financial reports more systematically, while employees can record transactions and print receipts automatically. System testing using the black-box method shows that all key features function as expected. With this information system, laundry businesses can improve operational efficiency, minimize recording errors, and enhance transparency in financial management. It is expected that this system can serve as a solution for small and medium enterprises to adopt information technology and increase their competitiveness in the digital era.